Projeto - Reaproveitar é preciso: brinquedos e brincadeiras com sucatas - Santos, Ana Paula de Souza; Ferreira, Eleuza Espíndola; Bento, Miriam Furtado; Couto, Silvana Bento de Melo; Schiavinato, Ricardo Leandro; Teles, Antônio Miguel Bianco; Lima, Eliene Xavier de; Quadros, Izabel Cristina Rezende de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> VER PDF